Duration of land rights in the capital city of the Nusantara: The Perspective of national agrarian law - Suyanto Suyanto (Trigin Publisher, 2023)
Government Regulation Number 12 of 2023 concerning the Granting of Business Permits, Ease of Doing Business and Investment Facilities for business actors in the National Capital of the Nusantara (IKN), there are legal issues regarding the regulation of the granting of tenure of 95 to 190 years of leasehold rights, building use rights above right of authority management in IKN, for 80 years to 160 years. This study uses normative research using statutory approaches, conceptual approaches and philosophical approaches. The granting of a period of land rights originating from internal management rights as stipulated in Articles 18, 19 and 20 of Government Regulation Number 12 of 2023 which regulates firstly, the period for granting land rights, secondly, HGU or HGB and usage rights are stated in a Letter decision granting rights.